EARLY MANAGEMENT OF SEVERE PRE-ECLAMPTIC AND ECLAMPTIC REFFERAL PATIENT AT KOTABARU REGENCY - Winarty Natalia Hasibuan; Muhammad Ardian Cahya L; Budiono Budiono (Indonesian Midwifery and Health Sciences Journal, 2020)
ABSTRACTBackground: The maternal mortality rate is 305 per 100,000 live births in Indonesia. The most common cause of maternal death is preeclampsia / eclampsia. The maternal mortality rate is 247 per 100,000 live births in 2017 in Kotabaru Regency. Most preeclamptic referral patients are in critical condition when they arrive at the hospital. Method: This type of research is an observational descriptive study. The population is all patients with severe preeclampsia and eclampsia in the delivery room of RS Pangeran Jaya Sumitra Kabupaten Kotabaru from January - December 2018. The sample is total sampling.Results: PEB referral patients was 57 cases. Most of those are in the group age of 20 - 35 years which are 35 people (61.4%), not nullipara is 31 people (54,4%), 34-40 weeks of gestation is 43 people (75,4%), as many as 44 people (77,2%) with previous severe preeclampsia/ hypertension, 41 people (71,9%) brought referral letters, referred by Puskesmas are 47 people (82.5%), most of the locations of referral is from Pulau Laut as many as 35 referrals (61,4%). The initial management of PEB and eclampsia: IV Pathway in 11 patients (19.3%) of severe preeclamptic and eclamptic patients, 50 patients (87.7%) were not given MgSO4, 51 people (89.5% ) did not get anti-hypertension, 52 patients (91.2%) were not installed catheters. Conclusion: Early management of severe preeclamptic and eclamptic patients is not optimal and does not fulfil the standard yet. Proper and appropriate early management can reduce morbidity and maternal mortality from complications of severe preeclampsia and eclampsia that can be prevented by providing right initial management.